Protestantism and the secularisation of marriage in France: historical and ethical approaches - Johner, Michel (European journal of theology, 2015)
Michel Johner provides a brief historical overview of the forms of marriage in France in the last 400 years, before discussing the question whether a religious marriage without a civil marriage is at ail possible. He defends a negative answer to that question with the following arguments: in Protestant theology, marriage is seen as a civil and political act; in the case of divorce and remarriage, the marriage bond has to be recognised in civil law; the filiation of children who inherit needs to be properly ascertained. The author then examines how Christians can combine a civil marriage and a Christian marriage so that when they marry, they honour both the national laws and Cod's laws. Ways in which Christians can supplement civil weddings are suggested. As some Christians are likely to object to this approach of accommodation, which relies on a strict distinction between what is authorised and what is imposed, the article concludes with a discussion of possible objections